HASIL BELAJAR IPS TERPADU MELALUI GI DAN PBL MEMPERHATIKAN KEMAMPUAN BERPIKIR KREATIF - Eka Setiawati; Yon Rizal; Nurdin Nurdin (FKIP Unila, 2015)
Seeing the learning results which were not optimal, the change in the learning process which created an atmosphere of active learning and fun should be started to be applied in schools. This study aimed to determine the effectiveness of the implementation of cooperative learning, GI and the PBL if being associated with creative thinking abilities of the students in the Social Studies subjects. The method used was a quasi-experiment. The hypothesis testing used Two Way Analysis of Variance (ANOVA) and t-test of two independent samples. The results showed that there was a significant difference in learning outcomes through the Social Studies for GI model and the type of PBL. There was also a significant interaction between learning model with creative thinking abilities of students.Melihat hasil belajar yang belum optimal, maka perubahan dalam proses pembelajaran yang menciptakan suasana belajar yang aktif dan menyenangkan seharusnya mulai diterapkan disekolah.Penelitian ini bertujuan untuk mengetahui keefektifan penerapan model pembelajaran kooperatif tipe GI dan tipe PBL jika dikaitkan kemampuan berpikir kreatif yang dimiliki siswa pada mata pelajaran IPS Terpadu. Metode yang digunakan eksperimen semu. Uji hipotesis menggunakan Analisis Varians Dua Jalan ( ANAVA ) dan T-test dua sampel independen. Hasil penelitian menunjukaan ada perbedaan yang signifikan hasil belajar IPS Terpadu melalui model pembelajaran GI dan tipe PBL dan ada interaksi yang signifikan antara model pembelajaran dengan kemampuan berpikir kreatif siswa.Kata kunci : hasil belajar, GI, KBK, PBL